An overview of CBDCs and their potential role in the green economy [version 1; peer review: 1 approved, 2 approved with reservations] - Konstantinos Alexakis; Vangelis Marinakis; Paanagiotis Kokkinakos; Christos Kontzinos; Fotis Siouzos; Maria Flouri (Open Research Europe)
In recent years, there has been an ever-intensifying discussion around the use and establishment of Central Bank Digital Currencies (CBDC) in the global economy. This paper examines the reasons why central banks are aiming to introduce CBDCs into the economy, as well as the ways in which the use of CBDCs could contribute to the transition to the Green Economy, focused mainly around the area of providing financial means and incentives towards green investments, green renovations, and more sustainable energy consumption practices. Aiming to provide an all-around and concise overview of CBDCs, this paper explores their technological background, as well as the areas in which they will mainly contribute, as a means of transaction or value storage. Special mention is also made of the initiatives undertaken by the European Central Bank for the issuance of the digital euro as well as the legal and technological framework within which it could operate, to serve the objectives of the EU. Finally, the potential role of CBDCs in the green economy is examined, and ways in which they could be used as a means of supporting individuals and businesses investing in this direction are presented. This publication is written in the context of the Horizon Europe funded project FORTESIE.